2022
DOI: 10.1002/syst.202100051
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Crowding and Intrinsically Disordered Proteins: A Polymer Physics Perspective

Abstract: The cell is a crowded environment where a relevant fraction of the available space is occupied by proteins, nucleic acids, and metabolites. Here we discuss recent advancements in the understanding of crowding effects on intrinsically disordered proteins. Differently from their structured counterparts, these proteins do not adopt a stable three-dimensional structure and remain flexible and dynamic in solution. The physics of polymers and colloids provides a framework to interpret how crowding modulates conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 175 publications
(326 reference statements)
2
27
0
Order By: Relevance
“…The ratio between charge and hydropathy (commonly referred to as, C/H) of IDPs regulates the extent of compactness. , Using different IDPs having varied amino acid sequences, Choi et al. characterized their molecular dimensions from smFRET measurements .…”
Section: Targeting Rapid Conformational Plasticity Of Idpsmentioning
confidence: 92%
See 3 more Smart Citations
“…The ratio between charge and hydropathy (commonly referred to as, C/H) of IDPs regulates the extent of compactness. , Using different IDPs having varied amino acid sequences, Choi et al. characterized their molecular dimensions from smFRET measurements .…”
Section: Targeting Rapid Conformational Plasticity Of Idpsmentioning
confidence: 92%
“…18 Thus, molecular crowders in the structural transitions of IDPs serve as reasonable mimicking agents under in vitro conditions, thereby enabling us to draw a scientific analogy with the conditions encountered in the in vivo environments. 18,19 Schuler and co-workers quantified the role of crowding induced by common polymers. 10 They demonstrated that a reduction in the structure of IDPs occurs upon increasing the concentration and the size of the crowder.…”
Section: Conformational Dynamics Of Idpsmentioning
confidence: 99%
See 2 more Smart Citations
“…The large spectrum of scaling exponents observed under native conditions for different unfolded and disordered proteins [53,64,70,71] reflects the contribution of sequence composition on the conformations of disordered ensembles. Müller-Späth et al [72] used single-molecule FRET to probe the conformations of unfolded proteins, showing the degree of compaction and expansion of the interdye distance depends on the charged residue content in the protein, and acceptor-acceptor (AA) exhibits a correlated decay, whereas the cross-correlation (AD) shows an anticorrelated increase in the signal.…”
Section: Effect Of Sequence On Chain Conformationsmentioning
confidence: 99%